2012
DOI: 10.1051/0004-6361/201118724
|View full text |Cite
|
Sign up to set email alerts
|

New measurements of rotation and differential rotation in A-F stars: are there two populations of differentially rotating stars?

Abstract: Context. The Sun displays differential rotation that is intimately connected to the solar dynamo and hence related to solar activity, the solar cycle, and the solar wind. Considering the detectability and habitability of planets around other stars it is important to understand the role of differential rotation in other stars. Aims. We present projected rotational velocities and new measurements of the rotational profile of some 180 nearby stars with spectral types A-F. The results are consolidated by a homogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 29 publications
7
44
1
1
Order By: Relevance
“…These authors predicted a very strong temperature dependence (dΩ ∝ T 8.9 eff ), which is not supported by our measurements. Light blue diamonds show measurements 7 from Ammler-von Eiff & Reiners (2012) that are in good agreement with our findings. Theoretical predictions from Küker & Rüdiger (2011) are shown as dash-dotted red and dashed orange curve.…”
Section: Differential Rotationsupporting
confidence: 88%
“…These authors predicted a very strong temperature dependence (dΩ ∝ T 8.9 eff ), which is not supported by our measurements. Light blue diamonds show measurements 7 from Ammler-von Eiff & Reiners (2012) that are in good agreement with our findings. Theoretical predictions from Küker & Rüdiger (2011) are shown as dash-dotted red and dashed orange curve.…”
Section: Differential Rotationsupporting
confidence: 88%
“…Using the Fourier transform method Reiners & Schmitt (2003) also found that α increases with rotation period for F-G stars. This result was confirmed by Ammler-von Eiff & Reiners (2012) who compiled previous results and new measurements for A-F stars. Barnes et al (2005) found that ΔΩ only weakly correlates with rotation rate according ΔΩ ≈ Ω 0.15 .…”
Section: Fig 16 Comparison Of Periods Fromsupporting
confidence: 74%
“…Reiners & Schmitt 2002Ammler-von Eiff & Reiners 2012, and references therein). For HD 105382 and HD 131120, Briquet et al (2004) obtained v sin i = 70 ± 5 and 60 ± 5 km s −1 , respectively, from modelling of He and Si surface spots by assuming constant surface rotation.…”
Section: Rotational Velocities From Spot Modelling or Asteroseismologymentioning
confidence: 99%